Burger's Medicinal Chemistry and Drug Discovery 2010
DOI: 10.1002/0471266949.bmc124
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Chemistry Approaches for Multitarget Drugs

Abstract: It has become increasingly well recognized that modulating multiple biological targets in parallel can be beneficial for treating diseases with complex etiologies such as cancer, asthma, and psychiatric diseases. Both screening and knowledge‐based strategies have been used for generating ligands with a specific multitarget profile (designed multiple ligands or DMLs). DML projects are often challenging for medicinal chemists, with the need to appropriately balance affinity for two or more targets while obtainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The framework combination strategy has been already successfully applied in drug discovery to develop multifunctional drugs that have been approved for human clinical use. 35 On the basis of this strategy, we have previously successfully identified several series of druglike multifunctional ligands acting on a defined set of serotonin and dopamine receptors, with a representative molecule 1 portrayed in Figure 1 . We found that the superimposition of the selective 5-HT 7 receptor antagonist, SB 258719, with the potent 5-HT 6 receptor antagonist, SB214111, showed a remarkable overlap of the pharmacophore features to yield a common N -(3-(piperidin-1-yl)propyl)benzenesulfonamide fragment, with molecular recognition for both 5-HT 6 and 5-HT 7 receptors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The framework combination strategy has been already successfully applied in drug discovery to develop multifunctional drugs that have been approved for human clinical use. 35 On the basis of this strategy, we have previously successfully identified several series of druglike multifunctional ligands acting on a defined set of serotonin and dopamine receptors, with a representative molecule 1 portrayed in Figure 1 . We found that the superimposition of the selective 5-HT 7 receptor antagonist, SB 258719, with the potent 5-HT 6 receptor antagonist, SB214111, showed a remarkable overlap of the pharmacophore features to yield a common N -(3-(piperidin-1-yl)propyl)benzenesulfonamide fragment, with molecular recognition for both 5-HT 6 and 5-HT 7 receptors.…”
Section: Resultsmentioning
confidence: 99%
“…In this approach, the degree of framework overlap is systematically increased until the frameworks overlap maximally to give the simplest single molecule, with druglike properties. The framework combination strategy has been already successfully applied in drug discovery to develop multifunctional drugs that have been approved for human clinical use . On the basis of this strategy, we have previously successfully identified several series of druglike multifunctional ligands acting on a defined set of serotonin and dopamine receptors, with a representative molecule 1 portrayed in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Since 2004, Morphy et al. started to systematically review strategies for multifunctional ligands development. MTDLs are agents that treat multifactorial diseases by interacting with multiple targets involved in pathogenesis . This strategy could avoid many pitfalls. In Table , the advantages and disadvantages of the above two approaches are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The rational design of multitargeted compounds is challenging, especially when attempting to merge multiple molecular frameworks and the corresponding underlying pharmacophores in a single small molecule. 32 However, a series of fungicidal diaryl-pyrazoles (e.g., 1 , Figure 1 ) and -imidazoles (e.g., 2 , Figure 1 ) with known MT-stabilizing activity exhibit tricyclic structures similar to those found in known nonsteroidal anti-inflammatory drugs (NSAIDs) such as the potent COX-1 inhibitor 33 SC560 ( 3 , Figure 1 ) and, to a lesser extent, the dual COX/5-LOX inhibitor 34 licofelone ( 4 , Figure 1 ). Furthermore, molecular docking studies indicated that selected representative examples of these MT-stabilizing imidazoles could fit within the arachidonic acid binding site of COX-1 with a predicted binding energy that is comparable (i.e., within 2 kcal/mol) to that of 3 (see Figure 1 and Supporting Information ).…”
Section: Introductionmentioning
confidence: 99%
“…The rational design of multitargeted compounds is challenging, especially when attempting to merge multiple molecular frameworks and the corresponding underlying pharmacophores in a single small molecule . However, a series of fungicidal diaryl-pyrazoles (e.g., 1 , Figure ) and -imidazoles (e.g., 2 , Figure ) with known MT-stabilizing activity exhibit tricyclic structures similar to those found in known nonsteroidal anti-inflammatory drugs (NSAIDs) such as the potent COX-1 inhibitor SC560 ( 3 , Figure ) and, to a lesser extent, the dual COX/5-LOX inhibitor licofelone ( 4 , Figure ).…”
Section: Introductionmentioning
confidence: 99%